Online Physical Therapy Protocol Quality, Variability, and Availability in Achilles Tendon Repair. Issue 1 (February 2019) - Lightsey, Harry M.; Noback, Peter C.; Caldwell, Jon-Michael E.; Trofa, David P.; Greisberg, Justin K.; Vosseller, J. Turner
Background: Substantial progress has been made in characterizing the benefit of early functional rehabilitation following Achilles tendon repair (ATR). However, standardized ATR rehabilitation guidelines have yet to be produced. Furthermore, as patients increasingly use the Internet to independently retrieve health care content, access to standardized, clinically effective rehabilitation protocols is necessary. Methods: Online ATR physical therapy protocols from US academic orthopaedic programs were reviewed. A comprehensive scoring rubric was designed after reviewing all identified protocols and was used to assess each protocol for both the presence of various rehabilitation components as well as when those components were introduced. Results: Twenty-two of 155 US academic orthopaedic programs published postoperative Achilles rehabilitation protocols online, with a total of 27 individual protocols available for review. Twenty-one protocols (78%) recommended immediate postoperative splinting. Only one protocol recommended short-leg casting. Twenty-six protocols (96%) advised immediate nonweightbearing with progression to weightbearing as tolerated at an average of 3.0 weeks (range, 1-8 weeks) and to full weightbearing at an average of 7.3 weeks (range, 2-12 weeks). Active plantarflexion and dorsiflexion to neutral were included by most protocols (93%) at an average of 3.9 (range, 0-9) weeks and 3.4 (range, 0-8) weeks, respectively. There was considerable variability in the inclusion and timing of strengthening, stretching, proprioception, and basic cardiovascular exercises. Fourteen protocols (52%) recommended return to training after meeting certain athletic activity criteria. Conclusion: The purpose of this investigation was to evaluate the quality, variability, and patient accessibility of publicly available rehabilitation protocols for ATR provided by US orthoapedic teaching programs. To this end, we found that a minority of US academic orthopaedic programs publish ATR rehabilitation protocols online. While a trend away from traditional ankle casting is apparent, many programs have not adopted the accelerated weightbearing and controlled mobilization techniques that have been shown to produce better functional outcomes and greater patient satisfaction. There is also a substantial degree of variability in both the composition and timing of rehabilitation components across physical therapy protocols. Levels of Evidence: Level III: Retrospective comparative study